Xenopus laevis serum albumins are encoded in two closely related genes. - Westley, B (1981)
cDNA clones containing sequences complementary to Xenopus laevis albumin mRNA have been identified in a collection of cDNA clones made from poly(A)+ RNA prepared from male Xenopus laevis liver. Although all the albumin cDNA clones crosshybridise, restriction enzyme and heteroduplex analysis show that there are 2 closely related albumin mRNA sequences. The 2 albumin mRNAs are only mismatched by 8% but could be isolated by positive selection using stringent hybridization conditions. Oocytes injected with the 2 purified mRNAs, secreted either the 68,000 or 74,000 dalton albumin into the culture medium showing that the 2 albumins of X. laevis serum are encoded in the 2 closely related mRNAs. Measurements of the abundance of albumin mRNA show that the 2 albumin mRNAs together account for about 9% of total poly(A)+ RNA in male Xenopus laevis liver but the mRNA coding for the 74,000 dalton mRNA is about twice as abundant as that coding for the 68,000 dalton mRNA.